RUSSIA’S INTERESTS IN THE EASTERN PARTNERSHIP REGION: KEY CHALLENGES - Abrat, Serhiy (Public Management and Policy, 2025)
The article focuses on the study of the Russian Federation's key interests in the countries of the Eastern Partnership region. It is found that the main Russian interests in this region are historical, geopolitical, economic, security, ideological, and ethnic. Russia's interests in the Eastern Partnership region stem from the type of foreign policy of this state and the geopolitical concepts that underlie its main state activities. In particular, these are the imperial doctrine, the “Russian world” doctrine, and the concept of “hard power” as the basis for the implementation of Russian foreign policy. The author assesses Russia’s influence on each of the EaP countries. It is found that all six states have a significant influence on their domestic and foreign policies by the Moscow. Russia uses weapons, threats of force, separatism, ideology, energy blackmail, propaganda, cyberattacks, formation of pro-Russian forces, weakening of democracy, and corruption to maintain its influence in the EaP states. The most dependent state in the region is Belarus, which is actually under full Russian influence. Moldova and Ukraine are the least dependent, but force and other methods of influence are actively used to keep them in the sphere of Russian influence. The article examines the key challenges for the states of the region from Russia's influence, including the crisis of global and regional security systems, the Russian-Ukrainian war, conflicts in Transnistria, Abkhazia, South Ossetia and Nagorno-Karabakh, the energy and humanitarian crises in Europe, and the formation of pro-Russian forces in the region and the EU. In order to resolve the crisis in the Eastern Partnership region, it is important to provide security guarantees from the EU, NATO, and the US to those states that want them. It is also important to create a sustainable system of collective security, guarantees of peace and compliance with international law on a global scale. Integration of the Eastern Partnership states (some of them) into the EU and NATO could be a key to their withdrawal from Russia's influence. The intensification of economic development of these states will also serve as a successful option for breaking away from dependence on Russia.